Examining the robustness of market risk models - Roque, Roberto Miguel S.
Reviews Value at Risk (VaR) and Expexted Shortfall (ES), the current industry risk measures, and the usefullness of including Expectiles as a new measure of risk. Results can assist financial institutions, regulators, investors and researchers to gain insights on measuring risk. By acting prudently, financial institutions and regulators create a more stable financial environment which can lead to sustained economic growth and raise the standard of living for it.